A new month, a new data breach. Issue 3 (March 2016) - German, Paul
Abstract : The wave of data breaches washing over enterprises around the world has surfaced an essential truth about IT security – typical enterprise security architectures are vastly outmoded in terms of how modern applications are shared, managed and accessed by users. And with each month bringing a new data breach, the implications for both compromised employees and the wider infrastructure are significant.